Prentice Hall science explorer : (Pearson Prentice-Hall, 2005)
This book consists of the following five chapters: sponges, cnidarians, and worms; mollusks, arthropods, and echinoderms; fishes, amphibians, and reptiles; birds and mammals; animals behavior.